2000
DOI: 10.1002/1521-396x(200012)182:2<653::aid-pssa653>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Crystallinity of SiC Surface Layers Produced by Ion Implantation

Abstract: Carbon implantations into silicon were carried out in order to form thin surface layers of SiC. Single crystalline h100i silicon samples were implanted with 40 keV 13 C ions with a fluence of 3.8 Â 10 17 ions/cm 2 and subsequently thermally treated under high vacuum conditions at different temperatures using a 20 keV electron beam. The isotope 13 C offers the advantage to measure the carbon redistribution caused by the thermal treatment process with the nuclear resonance reaction analysis. The crystallinity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The alteration of the 15 N depth profile during the thermal treating, from a Gaussianlike nitrogen depth distribution into a rectangular one, was also observed on carbonimplanted silicon samples being subsequently thermally treated just as under high vacuum conditions with scanned 20 keV electron beam [18][19][20]. It was demonstrated, that the carbon redistribution was not the result of a diffusion process, but of silicon etching as shown by an experiment with a depth marker [18].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The alteration of the 15 N depth profile during the thermal treating, from a Gaussianlike nitrogen depth distribution into a rectangular one, was also observed on carbonimplanted silicon samples being subsequently thermally treated just as under high vacuum conditions with scanned 20 keV electron beam [18][19][20]. It was demonstrated, that the carbon redistribution was not the result of a diffusion process, but of silicon etching as shown by an experiment with a depth marker [18].…”
Section: Resultssupporting
confidence: 81%
“…In this article we report on the formation of a thin a-Si 3 N 4 surface layer after implantation of 60 keV nitrogen ions into silicon, when the implanted sample was thermally treated under high vacuum conditions. This work continues a former investigation, which demonstrated that thin b-SiC surface layers on silicon are formed by carbon implantation into silicon and subsequent thermal treatment under high vacuum conditions [18][19][20]. This formation process is caused by the process of active oxidation of silicon.…”
Section: Introductionmentioning
confidence: 99%
“…For example, implanting carbon ions in the energy range from 1.5 MeV to below 100 kV and postannealing at 1250°C in Ar or N 2 atmosphere, results in a buried crystalline ␤-SiC layer whose depth below the surface reduces with implantation energy. [6][7][8][9] However, even at low implantation energies, the SiC layer tends to lie below the substrate surface which, for many technological applications, necessitates a preliminary etching step to expose the buried SiC layer.…”
mentioning
confidence: 78%